2018
DOI: 10.1097/aud.0000000000000670
|View full text |Cite
|
Sign up to set email alerts
|

Early Sentence Recognition in Adult Cochlear Implant Users

Abstract: Normal-hearing subjects listening to acoustic simulations of cochlear implants (CI) can obtain sentence recognition scores near 100% in quiet and in 10 dB signal-to-noise ratio (SNR) noise with acute exposure. However, average sentence recognition scores for real CI listeners are generally lower, even after months of experience, and there is a high degree of heterogeneity. Our aim was to identify the relative importance and strength of factors that prevent CI listeners from achieving early, 1-mo scores as high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
83
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(87 citation statements)
references
References 57 publications
2
83
2
Order By: Relevance
“…Our research has shown that the main factors that influence performance are related to circumstances of etiology and duration of deafness, outcomes of surgical intervention of insertion depth and dislocation, and central aspects of linguistic and neurocognitive skills [1]. The variability seen in speech recognition scores are described in Tables 1 and 2.…”
Section: Preoperative Counselingmentioning
confidence: 87%
See 4 more Smart Citations
“…Our research has shown that the main factors that influence performance are related to circumstances of etiology and duration of deafness, outcomes of surgical intervention of insertion depth and dislocation, and central aspects of linguistic and neurocognitive skills [1]. The variability seen in speech recognition scores are described in Tables 1 and 2.…”
Section: Preoperative Counselingmentioning
confidence: 87%
“…If the etiology is not congenital, then the formula is only 90 minus half the number of years of HL. The predictive model is not valid for cases of labyrinthitis (e.g., chronic otitis and autoimmune disease), where the findings of [1] indicated considerable variability and generally poor outcomes. Our evidence from adults suggests a priori that those with congenital HL are expected to yield poor performance scores.…”
Section: Preoperative Counselingmentioning
confidence: 98%
See 3 more Smart Citations